Crym Girey I – the founder of the classical theater in the Crimea (on the issue of 257 years experience of the Crimean Tatar`s first theatrical productions of the European type theater). - Ismet Zaatov (Крымское историческое обозрение)
The formation process of the Crimean Tatar theater can be divided into the following periods: medieval – folk theater (the initial round dance and toy puppet theater of shadows “Karagoz”, the theater of one actor “meddah”, the arena theater “orta oyuny”); Khan`s theater in the middle of the XVIII century (penetration into the Crimea of European theater traditions in the era of the Crimean Khan Crym Girey I); the revival of traditions of the Crimean Tatar theater late XIX–XX centuries (the activities of a theater-goers group of the Jadidist Crimean Tatar youth–followers of I. Gasprinsky, under the leadership of J. Meinov – the efforts of the Crimean Tatar noblewoman-myrzachkas under the leadership of A. Taiganskaya; organization of a professional Simferopol Tatar theater troupe under the People’s Commissar of Education of the Crimean ASSR in 1921 and creation and activities of the Crimean Tatar Drama Theater, headed by A. Taigan, and the Crimean Tatar amateur movement in the Crimea, and among the Crimean Tatar foreign diaspora of 1923–1944 (Soviet pre-deportation period); recreation and current activities of the Crimean Tatar theater in the Crimea,1989 (post deportation period).